Proposta de um modelo teórico de transferência de tecnologia para o desenvolvimento sustentável de Smart Cities - Corsi, Alana (2020)
Faced with problems arising from rapid urbanization, population growth, and the current pattern of consumption, which causes resource depletion, climate change, and social, economic, and environmental impacts, there is pressure to devise strategies to minimize or mitigate them. them. Given this, sustainable development and its mechanisms are now widely addressed. The current action to promote sustainability is the 17 Sustainable Development Goals (SDGs) that propose means for its implementation. Among them is Technology Transfer. As a strategy to address the problems arising from cities and growing urbanization, the Smart Cities model, called Smart Cities, emerges, which focus on technological solutions for the essential services of cities. Although they are at the heart of several sustainability issues, some studies do not relate them to sustainable issues, making them a model of cities unaware of current problems. Therefore, there is a need to align both the Technology Transfer process and the Smart Cities model to achieve the Sustainable Development Goals. Thus, the objective of this study is to propose a theoretical Technology Transfer model for the sustainable development of Smart Cities. For this, a systematic literature review was performed in three bibliographic databases. From the review and content analysis the theoretical model was built, based on four phases: Planning; Make it feasible; Implement and Accompany, and composing 12 cyclic steps. From the use of the model, a more effective transfer process is expected, since the model anticipates the possible barriers mentioned in the literature, formulating strategies to overcome them, with a view to the mentioned opportunities, in order to obtain greater assertiveness in technology selection, negotiation, financial planning and implementation. The work was limited by not applying the proposed model. The contribution is the generation of knowledge and information for entities interested in Technology Transfer processes. It is suggested for future work to apply the model in the context of a Smart City, in order to verify its effectiveness.